A comparative analysis of some methods of evaluating diets of preschool children from low income families. - Limbo, Azucena B.
Existing methods of evaluating dietary quality involve much labor and time. There is a need for simpler and quicker methods for such purposes as nutrition surveillance or establishing baseline information prior to implementation of nutrition intervention projects when speed is more critical than accuracy or exactness. This study, therefore, looked into some existing simpler and quicker methods of evaluating dietary quality to determine their comparability to the traditional method of computing nutrient contents as well as finding out if any of the short methods could be used to predict nutritional status. A total of 60 randomly selected preschoolers of different nutritional levels (by Gomez classification) from low income families of Meycauayan, Bulacan, composed the subjects of the study. The data collected included demographic and socio-economic characteristics of the subjects, i.e. age height, weight and 1-day food intake using the 24-hour food recall. 4 methods of evaluating diet quality were used, namely: a short method of calculating nutrient content of food intake; dietary diversity score; diet rating; and calculating nutrient content by the traditional long method. The following were then analyzed: the difference between calculated nutrient values obtained using the short method and the long method; the relationships between dietary diversity score and nutrient content by the long method, and between dietary diversity score and diet rating; the agreement between the various methods in classifying diets according to broad quality catagories; and the correlation between dietary diversity score and nutritional status using height-for-age and weight-for-height. The results revealed that the long and short methods of nutrient computation yielded essentially the same results when express as percentage accuracy or percentage of the Recommended Dietary Allowance (RDA). Protein, calcium and niacin exceeded the RDA, vitamin A and iron were nearly adequate, while energy, riboflavin thiamine and ascorbic acid were the least adequate. However, in terms of absolute values, the short method gave slightly higher results for energy, protein, iron thiamine, riboflavin, niacin and ascorbic acid, and lower values for calcium and vitamin A, but only the difference for energy, protein, calcium and thiamine were statistically significant. In general, the nutrient adequacy ratio obtained by the long method tended to be higher with increasing dietary diversity scores especially for ascorbic acid. The overall diet quality expressed as mean adequacy ratio was significantly correlated with dietary score (r = 0.8286). The numerical values obtained for dietary diversity score and diet rating were very similar and were significantly correlated (r = 0.8130). The results of the test of agreement showed that the methods agreed significantly in broadly classifying diets according to quality categories. The best agreement was between dietary diversity score and the long method. Finally, dietary diversity score correlated well with nutritional status as determined by the Gomez classification (C = 0.4785, X2 = 17.82) but not by the water low classification (C = 0.2363, X2 = 3.43).